IMPROVED TECHNOLOGY OF ROW COTTON HARVESTING - R. I. Spevakov (Сельскохозяйственные машины и технологии, 2016)
Officially approved machine technology of raw cotton harvesting in the modern conditions of agricultural production in the Republic of Uzbekistan does not make possible to mechanize in maximum this process with receiving qualitative cotton in a short time. A harvesting technology is effective, if more than 85 percent of cotton bolls are opened, and cotton-picker makes two passes. Thus, the second pass is carried out right after the first, but in an opposite direction. The authors presented results of field experiments, drew practical conclusions. The developed technology of picking, which basis the patent RUZ is, considers new forms of managing. Farms received practical recommendations about picking row cotton with necessary quality in a short time. In general they will be acceptable and for other cotton republics, next to Uzbekistan (Kazakhstan, Turkmenistan, Tajikistan, Azerbaijan).